學校教師學習社群發展的個案研究 Case Study of the Development of Learning Community in School - 高博銓 Kao, Po-Chuan (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2009)
學校的學習社群是教師自主性的專業組織，其發展有助於提升教師的專業知能，改善學生的學習成效。基於此，近年來有愈來愈多的學校領導人鼓勵校內教師成立學習社群。本文選擇一所推動學習社群的學校為樣本，針對個案學校內，一個由八位教師所組成的學習社群為對象，進行個案研究，探討其從學習社群成立到穩定發展的過程和經驗。研究的方法主要是採取觀察法、深度訪談、文件分析等方式，利用一年的時間蒐集所需的資料。研究結果顯示：(1)學習社群是鬆散且非正式的組織；(2)教師的滿意度可以提高其參與學習社群的動機；(3)學習社群所營造的成長文化具有催化作用；(4)學習社群的發展採取多元化的策略；(5)學習社群有助於促進學校教育的改革。 Learning community in school is an autonomous and professional organization which promotes teachers’ capacity of professional development and improves students’ learning outcome. Recently, more and more schools’ leaders encourage teachers to build learning community. The paper explores the school’s learning community composed by eight teachers as a selected sample and uses case study method. The case study presents the process and experience of learning community from the initial period to stabilized period. The research is conducted with observation, in-depth interview, and document analysis. It takes one year to collect the needed information. The research shows that (1) learning community is a loose and informal organization. (2) teachers’ satisfaction can boost their motivation. (3)climate of growth built by learning community is facilitative. (4) the development of learning community is through multiple strategies. (5) learning community can speed the reform of education.